Mechanisms of Batch Adsorption of Nickel (II) Ions from Aqueous Solution with Gossypium arboreum Shell Activated Carbon - Ganesan, Saravanakumar; Mani, Hema; Shanmugam, Arivoli (Asian Journal of Biological and Life Sciences, 2025)
Aim/Background: The effectiveness of an adsorbent made from Gossypium arboreum shell through acid treatment was evaluated in terms of nickel ion removal. Materials and Methods: Process variables that were investigated included agitation time, initial nickel ion concentration, adsorbent dose, pH, and temperature. The pace is mostly regulated by intra-particle diffusion, and the adsorption follows the second-order reaction equation. Freundlich and Langmuir isotherm models were applied to the equilibrium data. Results: The Langmuir isotherm plot's adsorption capacity (Qm) at 30, 40, 50, and 60±0.50ºC, starting at pH 6.5. The elimination of metal ions was significantly impacted by pH, and adsorption increased as temperature rose. Using 0.1M HCl, some of the Ni+ extracted from wasted APSNC. Conclusion: This work shows that Gossypium Arboretum Shell carbon may be used to extract Ni (II) ions.
Keywords: Equilibrium constant; Gossypium arboreum Shell Carbon (GASC); Isotherm Plot; Ni (II) ion